2006
DOI: 10.1038/sj.ki.5000162
|View full text |Cite
|
Sign up to set email alerts
|

Oxalobacter sp. reduces urinary oxalate excretion by promoting enteric oxalate secretion

Abstract: The primary goal of this study was to test the hypothesis that Oxalobacter colonization alters colonic oxalate transport thereby reducing urinary oxalate excretion. In addition, we examined the effects of intraluminal calcium on Oxalobacter colonization and tested the hypothesis that endogenously derived colonic oxalate could be degraded by lyophilized Oxalobacter enzymes targeted to this segment of the alimentary tract. Oxalate fluxes were measured across short-circuited, in vitro preparations of proximal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
201
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 19 publications
9
201
0
3
Order By: Relevance
“…Subsequently, using various approaches in rats, we demonstrated that Oxalobacter can modulate intestinal oxalate transport by inducing colonic oxalate excretion, and a consistent and beneficial consequence of this bacterial-enterocyte interaction was a significant reduction in urinary oxalate excretion due to this enteric oxalate shunt (15). These results are especially encouraging in the context of enteric oxalate elimination in PH1, where a deficiency in the liver enzyme alanine-glyoxylate aminotransferase (AGT) results in an enhanced endogenous burden of oxalate, leading to hyperoxaluria, oxalosis, and renal failure (5).…”
mentioning
confidence: 97%
“…Subsequently, using various approaches in rats, we demonstrated that Oxalobacter can modulate intestinal oxalate transport by inducing colonic oxalate excretion, and a consistent and beneficial consequence of this bacterial-enterocyte interaction was a significant reduction in urinary oxalate excretion due to this enteric oxalate shunt (15). These results are especially encouraging in the context of enteric oxalate elimination in PH1, where a deficiency in the liver enzyme alanine-glyoxylate aminotransferase (AGT) results in an enhanced endogenous burden of oxalate, leading to hyperoxaluria, oxalosis, and renal failure (5).…”
mentioning
confidence: 97%
“…[17][18][19][20][21][22][23][24][25][26] The bacterium is known to be susceptible to some antibiotics, 27 although the sensitivity pattern is incompletely characterized. The absence of O. formigenes could permit more absorption of dietary oxalate in the colon and decreased secretion from endogenous sources, 28 resulting in higher oxalate excretion in the urine and thus predisposition to CaOx calculus formation. Data from a number of relatively small studies show that patients with renal calculi and some conditions related to hyperoxaluria have a lower prevalence of O. formigenes in the stool than control subjects.…”
mentioning
confidence: 99%
“…Oxalobacter formigenes (O. formigenes) is an aerobic gram negative bacterium that uses oxalate as its energy source and decreases intestinal absorption of oxalate and thus reduces urinary oxalate excretion [34,35] . This has been well documented in both human and animal experiments [36,37] .…”
Section: Role Of Oxalobacter Formigenesmentioning
confidence: 99%